Risk Analysis Using Job Safety Analysis-Fuzzy Integration for Ship Maintenance Operation - Catur Wahyu Nugroho; Trika Pitana; Bagus Dinariyana (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2020)
Shipyard is an industry engaged in the maintenance and repair of ships and constructing a new ship. In ship repair operations, there are many activities in this operation. Propeller inspection, blasting, replating, welding, general work, electric work is an activity in ship repair operation. This research proposed a methodology to risk analysis ship maintenance operation, integrating Job Safety Analysis (JSA) with Bayesian Network (BN) and Fuzzy Inferences System (FIS). JSA method is used to find the hazards and the consequences of the maintenance operation. BN is developed for probability calculating of likelihood factors. Meanwhile, the FIS is used as a method to calculate the risk level. The FIS using the Mamdani algorithm based on the expert’s knowledge and experience. The integration of three methods is used to complete the risk assessment for replating activities. The proposed method is used to find out the risk level of replating activity on ship maintenance. Based on the result, the proposed model is more accurate, precise, and flexible depending on the basic factor that influences the operation. It would help to reduce the potential accident on the operation. This proposed method could be the other option as a tool to calculate risk assessment in other operations.